Meeting Attendance Design Using Web-Based Qrcode On Diskominfo Kota Tebing Tinggi - M Fahri Aditya Nasution; Hanum, Latifah (Journal of Information Systems and Technology Research, 2022)
Attendance is an activity carried out by a person to prove himself or not present in a meeting. The current condition of the presence of the meeting in the High Cliff City Diskominfo is still done by manual handwriting. This is ineffective and efficient and causes inaccurate attendance data obtained,so a system is needed that makes attendance effective and efficient for employees of the agency. Therefore, the Meeting Attendance System Design was created using a Web-based QR Code with PHP programming language and MySQL database. The system was created aimed at facilitating the process of the presence of agency employees and making it easier for High Cliff Diskominfo in the data of employees who have done absenteeism. The system is made by utilizing QR Code technology to make it easier for employees to do attendance absences no longer write manuals but by only scanning QR Codes when for absence. The system created has a QR Code scanning feature from qr code that has been created in admin, for scanning can use a webcam on a Personal Computer(PC). The implementation of this QR Code, is expected to make the attendance system easier and is expected to facilitate employees of the High Cliff City Diskominfo in carrying out meeting absences.